Kidney disease in lupus is not always 'lupus nephritis' - Anders, Hans-Joachim (BioMed Central, 2013)
In lupus erythematosus, elevated serum creatinine levels and urinary abnormalities implicate a kidney disorder, which may not always be lupus nephritis as defined by the current classification of the International Society of Nephrology/Renal Pathology Society. The signs of renal dysfunction may be caused by lupusunrelated renal injury such as drug toxicity or infection or by lupus-associated mechanisms that are not part of the classification, such as minimal change nephrotic syndrome or thrombotic microangiopathy. The latter seems to complicate lupus nephritis more frequently than previously thought. An unbiased assessment of kidney disease in lupus requires a kidney (re-)biopsy to define the appropriate management.